IMPLEMENTASI PROGRAM DAKWAH SEBAGAI SARANA PENANAMAN NILAI PENDIDIKAN AGAMA ISLAM UNTUK PENINGKATAN AKHLAK DAN PRAKTEK IBADAH SISWA DI SMP 11 MARET KEC. AMBARAWA KAB. PRINGSEWU : Indonesia - muhtarom; Eri Purwanti; Ulfa Umurohmi (STIT PRINGSEWU, 2016)
Abstract The role of the planting program of Islamic education in public and private schools is still very minimal. Planting of Islamic education as there are only in environment of school that religion based. But in junior high school 11Maret Sumber Agung, whose status as private schools were able to bring the exclusive through the study religious invitation program. This Program able to increase attitude or morality of the students as well as the activities of worship student in school environment. The purpose of this study was to determine the role of religious invitation program on the attitudes or moral and religious practices of students in the school. This study uses a quantitative descriptive approach. The results of this study showed an increase in students' attitudes and moral and religious practices in school as many as 25% from 52.5% to be 77.5%. Abstrak Peran program penanaman pendidikan islam di sekolah umum dan swasta masih sangat minim sekali. Penanaman pendidikan agama islam seakan hanya ada dilingkungan sekolah yang berbasis agama. Akan tetapi di SMP 11 Maret Sumber Agung, yang statusnya sebagai sekolah swasta umum mampu memunculkan kekhasanya melalui kajian program dakwah keagamaan. Program initernyata mampu meningkatkan sikap atau akhlaq siswa serta kegiatan peribadatan siswa dilingkungan sekolah. Tujuan penelitian ini adalah untuk mengetahui peran program dakwah keagamaan terhadap sikap atau akhlak serta praktek ibadah siswa di sekolah. Penelitian ini menggunakan pendekatan deskriptif kuantitatif. Hasil dari penelitian ini menunjukkan adanya peningkatan sikap dan akhlak siswa serta praktek ibadah di sekolah sebesar 25% dari 52,5% menjadi 77,5%. Kata kunci: Dakwah, Akhlaq, Praktek ibadah.